PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, PENGELOLAAN ASET TETAP DAN PERAN INTERNAL AUDIT TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN DENGAN SISTEM PENGENDALIAN INTERN SEBAGAI VARIABEL MODERATING (Studi pada Pemerintah Provinsi Riau) - Jumavis Irvia Saputra; Amir Hasan; Muhammad Rasuli (PEKBIS, 2020)
In the BPK-RI inspection report (LHP) on the Riau Provincial Government's financialstatements for 2017 there are still many findings related to internal control systemsand issues of non-compliance with statutory provisions. The purpose of this studywas to analyze the influence of human resource competencies, utilization ofinformation technology, management of fixed assets and the role of internal audit onthe quality of financial statement information with an internal control system as amoderating variable in the Riau Provincial Government. The population in this studyare officials or employees involved in the management of regional finances in theRegional Apparatus Organization (OPD) of Riau Provincial Goverment. Thesampling technique in this study using saturated or census sampling, with totalsample 120 (one hundred and twenty) people/respondents. The data collectionmethod is using survey method, data sources is using primary data and dataanalysis to test hypotheses is using multiple regression analysis. Research resultsshow that human resource competency, information technology utilization,management of fixed assets and the role of internal audit partially influence thequality of government financial statement information, internal control systemsmoderate the influence of fixed asset management and the role of internal audit ongovernment financial statement information quality, while internal control system isnot able to moderate the influence of human resources and the use of informationtechnology on the quality of government financial statement information.